PERAN BUDAYA SEKOLAH UNTUK MENCIPTAKAN LINGKUNGAN BELAJAR YANG KONDUSIF - Acep Rahmat Acep Rahmat; Munna Khoirunnisa; Siti Juariah; Taofiq Rudiansyah (Yayasan Al-Afif, 2024)
A positive school culture can enhance students' motivation and academic performance, while an inclusive curriculum ensures that all students have access to learning materials tailored to their abilities and needs, creating a more supportive and equitable learning environment. The aim of this study is to explore how school culture influences the development of a supportive learning environment and how such an environment can improve the quality of education and student outcomes. Data for this study was collected from credible and relevant sources. Qualitative analysis techniques (content analysis) were employed to categorize and further analyze the collected data to identify patterns or key themes. To determine the relationships between school culture, the creation of a supportive learning environment, and the factors contributing to the development of school culture, the results of the data analysis were evaluated. The findings indicate that an inclusive, cooperative, and student-centered school culture can foster a positive learning environment. Furthermore, school culture is significantly influenced by factors such as communication, leadership, and the involvement of parents and students.